Polysaccharides from Radix Peucedani: Extraction, Structural Characterization and Antioxidant Activity - Jie Zhang; Chenyue Wang; Qian Li; Wei Liang (Molecules, 2023)
In this study, an ultrasound-assisted green extraction method was applied for the extraction of polysaccharides from Radix Peucedani based on deep eutectic solvents (DESs), and the result showed that a DES system composed of betaine and 1,2-propylene glycol with a molar ratio of 1:2 possessed the optimal extraction efficiency for polysaccharides. Single-factor and Box–Behnken designs were used to determine the optimum extraction conditions for the maximum yields of polysaccharides from Radix Peucedani by using DESs. The maximum yields of polysaccharides attained 11.372% within a DES water content of 19%, an extraction time of 36 min, an extraction temperature of 54 °C, a solid–liquid ratio of 1:30 and an ultrasonic irradiation power of 420 W. The physicochemical properties of polysaccharides were analyzed using ICS and FT-IR, and the structure morphology was observed by SEM. The polysaccharides extracted from Radix Peucedani exhibited general antioxidant activities in vitro including DPPH, Hydroxyl and ABTS+ radical-scavenging activity. The antioxidant mechanism of Radix Peucedani polysaccharides was investigated using network pharmacology and molecular docking methods. The result showed that the high binding activity of glucose and IL1B, galactose and CASP3 was recognized as a potential mechanism for the antioxidant effects of Radix Peucedani polysaccharides.